Tinjauan Awal: - Herawati Herawati (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2017)
Wangsalan is an expression or speech that is similar to a puzzle or cangkriman, but the answer is already mentioned in answer line implicitely. Wangsalan basically consists of two parts: part 1 and part 2. Part 1 shows a sort of puzzle, couplet, or cangkriman / a guess, while part 2 shows some kind of answer or wangsalan content of the first part puzzle. The cangkriman understanding need to be explained for showing distinct differences between wangsalan and cangkriman. Cangkriman is an expression as structured in ordered words, in which the purpose or content has meaning to guess. For preliminary review of Javanese wangsalan pragmatic study is used. Pragmatics is one of sign system aspects beside syntactic and semantic aspects. Pragmatics examines the relationship between signs - including lingual sign–and the user in a speech concrete situation. The problem studied in wangsalan, namely (1) how to reveal semantic indicators between the part that contains puzzle and the section that states wangsalan contents, (2) how the relationship is built, distinctive nature of language usage which includes line setting, and (3 ) how is the utterances linkage between the first part (puzzle) and the second part (wangsalan content). Pragmatically, wangsalan in repertoire of New Javanese literature has certain functions in accordance with cultural value of Javanese society. Based on the data found on wangsalan, in general Javanese community in delivering advice, notice, petition, insinuation, warning/ban, and mockery to second party or other party is indirect.